Incidental intracranial saccular aneurysm in a patient with post-Covid-19 headache: What to do with the incidentaloma? - Valença, Marcelo Moraes; Silva, Alberto Henrique Torres Trindade da; Mendes, Renan Furtado de Almeida; Andrade, Pedro Henrique Pereira de; Silva, Ubiratan Alves Viturino da; Carvalho, Déborah Emmily de; Batista, Laécio Leitão (Headache Medicine, 2021)
Case report